Modelling of Moisture Movement in Wood during Outdoor Storage - Baronas, R.; Ivanauskas, F.; Juodeikienė, I.; Kajalavičius, A. (Nonlinear Analysis: Modelling and Control, 2001)
A model of moisture movement in wood is presented in this paper in a two-dimensional-in-space formulation. The finite-difference technique has been used in order to obtain the solution of the problem. The model was applied to predict the moisture content in sawn boards from pine during long term storage under outdoor climatic conditions. The satisfactory agreement between the numerical solution and experimental data was obtained.
Keywords: Wood storage; wood drying; modelling; diffusion; pine